Study of Airfoil Characteristics on NACA 4415 with Reynolds Number Variations - Waridho Iskandar (PRAISE WORTHY PRIZE, 2022)
This study uses computational methods to analyze fluid flow characteristics NACA 4415 in ultra-low, low, and moderate Reynolds number categories. The turbulence model chosen is the standard k-ε. The ultra-low Reynolds number used is 5×103, while the Reynolds number for the low category is 4.17×104. For the moderate category, the Reynolds number is 3×106. The variation of the grid being tested is the grid with the number of elements 5×104, 105 and 2×105. The grid with the number of elements 2×105 gives the best results. At the ultra-low Reynolds number, there is no stall condition. The stall condition at the low Reynolds number is AoA=12°. At the moderate Reynolds number, the stall occurs at AoA=18°. The largest Cl is in the moderate Reynolds number. Meanwhile, the smallest Cd is at the ultra low Reynolds number. Based on the analysis of pressure contours, velocity contours and velocity streamlines, the fluid flow patterns seen are not much different. However, there is a significant difference in their values.